Strategic Factors That Influence the Operations of the Gem and Jewelry Export Business in the New Normal Era in the Post-covid-19 World: Strategic Factors That Influence the Operations of the Gem and Jewelry Export Business in the New Normal Era in the Post-covid-19 World - Prangngampleng, Nattaporn; Komonsin, Laddawan (RATANABUTH JOURNAL, 2024)
Strategic Factors Influencing the Operations of the Gem and Jewelry Export Business in the New Normal Era in the Post-COVID-19 World. This research aims to 1. To test the consistency of the model measuring external and internal latent variables of strategic factors influencing the operations of gemstone and jewelry export businesses in the New Normal era in the post-COVID-19 world. 2. To test the research hypothesis on strategic factors influencing the operations of gemstone and jewelry export businesses in the New Normal era in the post-COVID-19 world. This research is quantitative, using questionnaires collected from a sample group of 400 employees and executives from gem and jewelry export businesses. The data was analyzed using descriptive statistics, which included frequency, percentage, mean, and standard deviation, along with structural equation modeling (SEM). The results of the model, after adjustments, showed that it aligned with empirical data based on the conceptual framework and theories used. The research findings on strategic factors influencing the operations of the gem and jewelry export business in the New Normal era in the post-COVID-19 world revealed that the goodness-of-fit index (GFI) and the adjusted goodness-of-fit index (AGFI) were 0.96 and 0.93, respectively, which are higher than 0.82 and approach 0.79. The RMSEA value was 0.013, which is less than 0.086.